Nutrition and type 2 diabetes etiology and prevention - Pereira, Mark A. (CRC Press/Taylor & Francis, 2014)
Focusing on the worldwide impact of type 2 diabetes regarding nutrition, dietary modification, risk, and management, this book draws on evidence-based research and provides numerous epidemiologic cohort studies, as well as carefully conducted clinical trials. Chapters correlate treatment modes and risk factors as well as the global impact of nutrition back to the basic premise held in the etiology of the disease. Topics include historical perspectives; macronutrients, micronutrients, food, dietary beverages, and dietary patterns; diet-gene interactions; and the role of age, ethnicity, and other demographics in modifying treatment for type 2 diabetes.